(untitled) (Revista Direitos Humanos e Democracia, 2021)
The purpose of this paper is to concern the criteria used by Federal Court of Justice to solve conflicts (and balance) between press freedom and personality rights, more specifically the right to honor. To this end, a thorough examination will be carried out on the parameters mentioned by Minister Luís Roberto Barroso on the Constitutional Complaint n. 22328 / RJ, which will also be examined the more flexible position of Supreme Court in admitting a Constitutional Complaint when there is an affront to the press freedom and by allowing, also atypically, the transcendence of the determining motives in processes related to that fundamental right.